2021
DOI: 10.1088/1742-6596/2051/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sintering temperature on composite hollow fibre membrane derived from hydroxyapatite cow bone and kaolin

Abstract: A modern application of composite hollow fibre membrane derived from hydroxyapatite cow bone and kaolin has been developed in wastewater treatment. The common fabrication method, a process that combined both phase inversion and sintering technique was used to fabricate the membranes. The hollow fibers membrane were developed using the spinning process by using a dope that have ratio of 20:20 (kaolin:cow bone hydroxyapatite). The sintering temperature that used in this study are 1000 °C, 1100 °C, 1200 °C and 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It was observed that the increase in its kaolin content translated into a composite with high rebound energy and impact strength 49 . Previous studies have also utilized cow bone hydroxyapatite and kaolin as fillers in a polyethersulfone polymeric binder for the fabrication of a ceramic hollow fiber membrane 50,51 . These studies show that, apart from polyethersulfone, no other polymer has been used as a matrix in a composition containing both cow bone and kaolin fillers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the increase in its kaolin content translated into a composite with high rebound energy and impact strength 49 . Previous studies have also utilized cow bone hydroxyapatite and kaolin as fillers in a polyethersulfone polymeric binder for the fabrication of a ceramic hollow fiber membrane 50,51 . These studies show that, apart from polyethersulfone, no other polymer has been used as a matrix in a composition containing both cow bone and kaolin fillers.…”
Section: Introductionmentioning
confidence: 99%
“…49 Previous studies have also utilized cow bone hydroxyapatite and kaolin as fillers in a polyethersulfone polymeric binder for the fabrication of a ceramic hollow fiber membrane. 50,51 These studies show that, apart from polyethersulfone, no other polymer has been used as a matrix in a composition containing both cow bone and kaolin fillers. This is also the first study, to the best of the author's knowledge, that combines both polystyrene and cow bone as matrix and filler, respectively, in a composite.…”
Section: Introductionmentioning
confidence: 99%